ANALISIS VEGETASI TUMBUHAN PENGHASIL BUAH-BUAHAN DALAM KAWASAN TEMBAWANG DUSUN TOHO RABA DESA RASAN KECAMATAN NGABANG KABUPATEN LANDAK - Toni, Paulus; Herawatiningsih, Ratna; Sisillia, Lolyta (Universitas Tanjungpura, 2017)
Forest is an important natural resource for peopleâ€™s lives, including various fruits that have been used for food and other necessities. This research aimed to analyze Fruit-producing Plant Vegetations that people consume in Tembawang Area Dusun Toho Raba Desa Rasan Ngabang District Landak Regency. This research used survey method. The vegetation was analyzed by using line compartment method and the observation plots were placed according to purposive sampling, one of the most frequently used sampling technique in research. The transects were made of 3 lines with the space of 200 m between the lines; line 1 with a length of 360 m, line 2 with a length of 420 m, line 3 with a length of 460 m; and 62 observation plots.Â The total area of observation was 2.48 Ha. There were 46 types of plant pound at all growth levels. 23 types of Fruit-producing Plant found in observation plots were composed of 19 types of seedling stage, 18 types of saplings stage, 18 types of pole stage, and 20 types of tree stage.Keywords : Area of Tembawang, Fruits, Species Diversity, Trees